The flip side of coin, or the erotic underground of medieval culture - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The spiritual life of the Middle Ages is extremely polymorphic and by no means reduces to official Christian orthodoxy. In particular, the cultural setting that divides earthly love and celestial love at different poles of the value scale, varies in Medial culture across all possible registers, giving rise to a whole gamut of new meanings and contradictions in its various layers. The special voice sounds in medieval culture – the voice of a kind of erotic underground which is ideologically suppressed by orthodoxy and driven out of the area of cultural legitimacy, but has not been stopped.
Keywords: sexuality; axiological discredit; interpretational discredit; ousting from the zone of legitimacy; torn consciousness; cultural underground; forms of adaptation of sexuality; deformation of interpretations; inadequate forms of manifestation